2005
DOI: 10.1007/s11094-006-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of saponins from table beetroot and primary evaluation of their pharmacological activity

Abstract: Saponins have been isolated by means of alkaline extraction from table beetroot. It is established that the introduction of a preliminary extraction stage eliminates the problem of removal of lipophilic components. Primary estimates of the adaptogen activity of beetroot saponins have been obtained by the method of external adverse factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 1 publication
0
17
0
1
Order By: Relevance
“…Beetroots (Beta vulgaris) are rich in valuable, active compounds such as carotenoids (Dias et al, 2009), glycine betaine, (de Zwart et al, 2003), saponins (Atamanova et al, 2005), betacyanines (Patkai et al, 1997), folates (Jastrebova et al, 2003), betanin, polyphenols and flavonoids (Váli et al, 2007). Therefore, beetroot ingestion can be considered a factor in cancer prevention (Kapadia et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Beetroots (Beta vulgaris) are rich in valuable, active compounds such as carotenoids (Dias et al, 2009), glycine betaine, (de Zwart et al, 2003), saponins (Atamanova et al, 2005), betacyanines (Patkai et al, 1997), folates (Jastrebova et al, 2003), betanin, polyphenols and flavonoids (Váli et al, 2007). Therefore, beetroot ingestion can be considered a factor in cancer prevention (Kapadia et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Many saponins are known to exhibit biological activity, such as antiviral, antidiabetic, cytotoxic, or allelopathic activity, etc., which makes those two substances, and the plants containing them, interesting objects for pharmacological investigations [1,2,3,7,15,19]. [18] As part of our ongoing studies on the isolation and identification of triterpene saponins in the roots of red beet, we found that all the found compounds were glyco- (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…These colorful root vegetables help to protect against heart disease and certain cancers (colon cancer) (Kavalcova et al, 2015). Beetroots are rich in other valuable compounds such as carotenoids (Dias et al, 2009), glycine betaine (de Zwart et al, 2003), saponins (Atamanova et al, 2005), betacyanins (Patkai et al, 1997), folates (Jastrebova et al, 2003), betanin, polyphenols and flavonoids (Vali et al, 2007). Therefore, beetroot ingestion can be considered a factor in cancer prevention (Kapadia et al, 1996).…”
Section: Introductionmentioning
confidence: 99%